Dwelling with God: Eden and the Tabernacle in Jewish Theology - Patanan, Ferry; Akimas , Handreas Sudarmiko; Tanasyah, Yusak (Indonesian Journal of Religious, 2024)
The Garden of Eden is a garden that God placed in the Eden area. There is a view that says that the Garden of Eden is just a myth or symbol. But the writer of the book of Genesis has recorded emphatically that the Garden of Eden really did exist on Earth. The Garden of Eden was the place where the first humans were created by God, this place was an ideal and perfect place for the first humans, namely Adam and Eve, to continue their lives. This research is qualitative research, namely research in the nature of a literature review. The Garden of Eden is a unique phenomenon in various views of the Ancient Near Eastern era. In the view of the Jews, the Garden of Eden was the first Tabernacle on Earth, where God was present in the lives of Adam and Eve at that time. This study explores the theological and symbolic connections between the Garden of Eden and the Tabernacle (Mishkan) within Jewish thought, emphasizing how both spaces function as loci of divine presence and communion between God and humanity. Drawing upon biblical texts, rabbinic literature, and later Jewish commentaries, the paper argues that Eden serves as a primordial sanctuary—an archetype for sacred space that is later echoed in the construction and function of the Tabernacle. The parallels in language, structure, and ritual—such as the presence of cherubim, the centrality of divine glory (Shekhinah), and the role of priestly mediation—suggest a deliberate theological continuity. By framing the Tabernacle as a symbolic reentry into Eden, the paper highlights the enduring Jewish vision of holiness as a lived, spatial, and relational reality.